Cognitive skills and economic growth in the twenty-first century: Evidence from PISA and cognitive ability studies - Björn Boman (International Journal of Educational Research Open)
In recent years, some educational researchers have questioned the theory of a robust relationship between test scores in international large-scale assessments such as PISA and lagged economic growth. However, both the proponents and opponents of such a human capital approach have mainly focused on earlier growth patterns during the twentieth century. Hence, the current article analysed the relationship between PISA 2000 and economic growth in 2010–2019 for 31 countries, and composite cognitive skills for 80 countries and their relationships with economic growth in 2010–2019. The results indicate that PISA scores or other cognitive skill measures could to some extent predict economic growth between 2010 and 2019, even when controlling for a significant number of variables. In a consecutive analysis, the relations were substantially associated with Middle Eastern countries because many countries from this region experienced political instability and decreasing oil revenues throughout this period. Hence, it is possible that regional and contextual relationships affect these patterns.